2004
DOI: 10.1016/j.febslet.2004.05.086
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of intact dense core vesicles in neurites of NGF‐treated PC12 cells

Abstract: Exocytic fusion in neuroendocrine cells does not always result in complete release of the peptide contents from dense core vesicles (DCVs). In this study, we use fluorescence imaging and immunoelectron microscopy to examine the retention, endocytosis and recycling of chromogranin B in DCVs of NGF-treated PC12 cells. Our results indicate that DCVs retained and retrieved an intact core that was available for subsequent exocytic release. The endocytic process was inhibited by cyclosporine A or by substitution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…We concluded that the internalized membrane is recovered to releasable vesicles in Ͻ2 min. This conclusion is in agreement with the recent findings by Bauer et al (8) in NGF-treated PC12 cells, by Henkel et al (21) in bovine chromaffin cells, and by Fulop et al (17) in mouse chromaffin cells. These authors have shown that internalized granules that resemble large dense core vesicles show up in ϳ2 min after exocytosis and become releasable in Ͻ5 min.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We concluded that the internalized membrane is recovered to releasable vesicles in Ͻ2 min. This conclusion is in agreement with the recent findings by Bauer et al (8) in NGF-treated PC12 cells, by Henkel et al (21) in bovine chromaffin cells, and by Fulop et al (17) in mouse chromaffin cells. These authors have shown that internalized granules that resemble large dense core vesicles show up in ϳ2 min after exocytosis and become releasable in Ͻ5 min.…”
Section: Discussionsupporting
confidence: 83%
“…It is commonly believed that the entire contents of dense core granules are released on exocytosis. However, existing evidence supports the notion that vesicles may actually release only a portion of these contents (1,3,8,9,32,37) before they are internalized (40). In pituitary lactotrophs, dense core vesicles undergoing exocytic fusion with the plasma membrane retained some nonsecreted prolactin in a dense core that was slowly internalized and then used during subsequent rounds of exocytosis (9).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, existing evidence supports the notion that vesicles might actually release only a portion of these contents (Alés et al, 1999;Artalejo et al, 1998;Bauer et al, 2004a;Taraska et al, 2003) before they are internalized. PC12 cells retain and retrieve their vesicle cores and make them available for subsequent exocytic release within <5 min (Bauer et al, 2004b). In chromaffin cells, one-third of the granules fuse in response to depolarization and reseal within 100 s (Perrais et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, kiss-and-run exocytosis could be a means to regulate quantal size, with the open time of the fusion pore determining the amount of neurotransmitter released per vesicle. Finally, during kiss-and-run exocytosis, LDCV retain their dense-core, which is made up of granins [255], thereby preventing graninmediated feedback. Consequently, factors that regulate the dynamics of the fusion pore or control the choice between full fusion and kiss-and-run exocytosis are critical for neurotransmission and are likely to play a role in synaptic plasticity [256].…”
Section: Endocytosis and Kiss-and-runmentioning
confidence: 99%